Five-coordination aluminum complexes: Synthesis, crystal structures and utilization for the construction of substituted guanidines. (1st February 2022) - Song, Qiuhong; Tong, Hongbo; Zhou, Meisu
Graphical abstract: Abstract: Insertion of 2, 6- i Pr2 C6 H3 N(Li)SiMe3 or PhN(Li)SiMe3 to the CN bond of Me2 NCN or PhCN afforded the lithium complexes [Li(2, 6- i Pr2 C6 H3 )NC(NMe2 )NC(NMe2 )N(SiMe3 )]2 (1a ) and [Li(PhNC(Ph)NSiMe3 )]2 (1b ). Complexes 1a and 1b were used as precursors to react with AlCl3 affording [(2, 6- i Pr2 C6 H3 )NC(NMe2 )NC(NMe2 )N(SiMe3 )]2 AlCl (2 ) and [(PhNC(Ph)NSiMe3 )]2 AlCl (3 ), respectively. The structures of 2 and 3 were presented. Both 2 and 3 exhibit good activity to catalyze the addition reaction of arylamines to N, N' -diisopropylcarbodiimide.